Protective effect of aqueous extracts from Taxillus chinensis (DC.) Danser on ovariectomy-induced osteoporosis in rats - WANG,Xiaoyan (2022)
Abstract As one of classic Chinese kidney-tonifying herbal medicines, Taxillus chinensis (DC.) Danser is widely applied in Chinese folk medicine as herbal tea for nutraceutical purposes including nourishing kidney, strengthening muscle and bone to against weakness, etc. In the present study, we investigated the protective effect of aqueous extracts from Taxillus chinensis (AETCs) on the ovariectomy (OVX)-induced osteoporosis in rats. Results showed that AETC treatment at the dose of 12.0 g raw materials/kg for 12 weeks significantly enhanced the bone mineral densities of femur and tibia, improved the trabecular microarchitecture compared with OVX controls. The serum levels of osteogenic markers alkaline phosphatase and osteocalcin were increased, and the levels of bone resorption biomarkers tartrate-resistant acid phosphatase 5b and telopeptides of collagen type I were suppressed by AETCs. Moreover, 12.0 g raw materials/kg AETC treatment significantly reduced the OVX-induced up-regulation of cyclooxygenase (COX)-2 mRNA and protein expression in bone tissues. Data suggested that AETCs showed anti-osteoporotic effect in OVX rats, possibly via promoting bone formation and inhibiting bone absorption. The down-regulation of inflammatory COX-2 might be involved in the protection of AETCs against OVX –induced osteoporosis.